The Philosophy of Systematic Sozology - Dołęga, Józef Marceli (Studia Ecologiae et Bioethicae, 2004)
The philosophy of systemic sozology presented in this work has as its characteristic originality under two aspects: metaobjective and objective. In the metaobjective aspect, here called the philosophy of sozology, one should underline the following elements: the elaboration of the notion - environment, the determining of the contents of the expression: social-natural environment, the elaboration of the definition of systemic sozology, the definition of the object of research of this discipline of science, the presentation of the structure, and especially the underlining of the importance of: interdisciplinarity, transdisciplinarity, systematics and globalism in the methodology of systemic sozology. In the objective or essential aspect the originality of the work is the underlining of the basic issues of systemic sozology and the presentation of them in six spheres, in which the process of life is realized, that it: the state of the social-natural environment, the sources of endangerment and pollution of the environment, the influence of the changing environment to life on Earth, the ways and means of protecting the environment.